Peningkatan Hasil Belajar Siswa Pada Pelajaran Matematika Melalui Media Tiga Dimensi di SDN Bekasi Jaya III - Dwi Estri Oktiana; Supardi U.S (PIJAR: Jurnal Pendidikan dan Pengajaran, 2024)
The educational process in schools focuses on teaching and learning interactions that aim to provide knowledge to students. Mathematics, as a fundamental discipline, contributes to the development of logical and critical thinking. The use of learning media, especially those based on technology and 3D, can improve students' interest and learning outcomes. This study uses the Classroom Action Research method consisting of planning, implementation, observation, and reflection. The primary data source is elementary school teachers. Data collection techniques use observation, interviews and documentation. Data analysis uses descriptive analysis. The results of the study showed a significant increase in student learning outcomes after the application of three-dimensional learning media, with the percentage of learning completion increasing from 14% in the pre-cycle to 81% in cycle II. This confirms that the use of appropriate learning media can improve the effectiveness of mathematics learning in schools.